Anglo-Saxon England - Stenton, F. M. (Frank Merry), 1880-1967 (Oxford history of England, 1971)
This classic history covers the period c. 550-1087 and traces the development of English society from the oldest Anglo-Saxon laws, the growth of royal power, and the extension of private lordship to the establishment of feudalism after the Norman Conquest.